Challenges of a Pandemic solidarity in Chile: contributions to an emerging theory - Román Brugnoli, José Antonio (2024)
This paper contributes to developing an emerging theory on the challenges and conditions of the possibility of pandemic solidarity through qualitative research contextualized in the Chilean case. Forty-eight in-depth interviews in four regions of Chile were analyzed following the principles of grounded theory. Through axial coding, an emerging theory is proposed to explore how the challenges of pandemic social solidarity are linked to the contextual framework of weakly institutionalized solidarity in which COVID-19 takes place and to the failures in the institutionalization of pandemic solidarity in public management. Finally, the relevance of these findings for potential future disasters of similar scope is discussed.